GEOLOGICAL AND ECONOMIC ASSESSMENT OF COAL DEPOSITS: CONTRASTING NATIONAL AND INTERNATIONAL TAXONOMIES IN ESTIMATING RESERVES AND RESOURCES - Рудько, Г.; Курило, М.; Бала, В. (Київський національний університет імені Тараса Шевченка, 2016)
The objective of the study is to examine major differences and similarities in domestic and international methodological approaches to estimating mineral resources base and assessing coal deposits. There is carried out a contrastive analysis of taxonomic criteria for coal deposits based on National Regulations and Australian Guidelines for Estimation and Classification of Coal Resources. Coal reserves having been analyzed in terms of quality and quantity (basic evaluation criteria) and factors that determine their commercial value having been identified, there is revealed a sufficient level of compliance with these criteria. However, there have been noticed cases of mismatch between assessable objects and their taxonomic nests, and hence, the suggestion is made to appropriate available geological information to every classifiable case. The study of the Guidelines reveals awareness of geological environment, commercial significance, and the extent of the feasibility analysis carried to be primary assessment criteria. The main differences in the criteria are recognized to lie in methods that validate assessment, for which direct statistical analysis and geo-statistical modeling of deposits are used in international practice. The practicability of the analysis suggested results in optimizing geological and economic evaluation of coal deposits by unifying different criteria. In the research there are compared the following options: Resource Categories (Measured, Indicated, Inferred Resources); Reserves Categories: A + B + C1 + C2; and Coal Reserves Categories, which are proven reserves. Comparison of the first group of quantitative indicators shows almost a complete match in volumes of previously explored and prospected reserves within all categories of Coal Resources. For categories of Coal Reserves and proven reserves there are significant differences resulting from the application of modifying factors to their definition in the case of JORC terminology. Coal Reserves values are more in line with quantity of commercial (recoverable) reserves - part of balance reserves, which are extracted taking into account project losses. In this case, quantity of recoverable reserves significantly exceeds Coal Reserves quantity. This is due to the fact that in national practice commercial reserves are assessed based on all quantity of previously explored and prospected categories, and Coal Reserves categories are based on the most reliable quantity of Indicated and Measured Resources.

Метою проведеної роботи є виявлення головних подібностей та розбіжностей методичних підходів при визначенні кількості запасів і ресурсів вугільних родовищ у вітчизняній і міжнародній практиці. Проведено співставлення класифікаційних ознак запасів і ресурсів вугільних родовищ для методичних рекомендацій, вітчизняних нормативних документів та Australian Guidelines for Estimation and Classification of Coal Resources. Проаналізовано параметри оцінки якості й кількості вугільних запасів та чинників, які визначають їхнє промислове значення. Встановлено достатній рівень відповідності цих параметрів. Визначено, що належність об'єкту оцінки до кожної з визначених груп класифікацій не завжди має точну відповідність і повинна оцінюватись у кожному конкретному випадку за наявною геологічною інформацією. У методичних рекомендаціях, які порівнюються в даній роботі, головними класифікаційними ознаками є ступінь геологічного вивчення, промислове значення (або відповідні модифікуючі чинники оцінки) та ступінь техніко-економічного вивчення. Головні відмінності між стандартами оцінювання запасів і ресурсів вугілля полягають в обґрунтуванні достовірності параметрів оцінки, для чого в міжнародній практиці використовують прямі вимоги щодо статистичного аналізу та геостатистичне моделювання родовищ. Практичнее значення такого аналізу полягає у спрощенні геолого-економічної оцінки вугільних родовищ, які розвідуються, за різними стандартами геологічного вивчення. Згідно з переліком ознак класифікацій для даного випадку доречним є порівняння таких пар: категорії ресурсів (Measured, Indicated, Inferred Resources) – запаси категорій А+В+С1+С2; категорії Coal Reserves – розвідані запаси. В порівнянні перших кількісних показників виявлено майже точне співпадіння обсягів розвіданих і попередньо розвіданих запасів із усіма категоріями Сoal Resources. Для категорій Coal Reserves і розвіданих запасів є істотні відмінності, пов'язані із застосуванням модифікуючих факторів для їх визначення у випадку термінології JORC. Згідно з визначеним переліком факторів, значення Coal Reserves більше відповідають кількості промислових запасів – частини балансових запасів, яка вилучається з надр. У даному випадку промислові запаси із числа балансових істотно перевищують обліковані кількості Coal Reserves. Це пояснюється тим, що у вітчизняній практиці промислові запаси розраховують, базуючись на всіх кількостях розвіданих і попередньо розвіданих категорій, а зарубіжні категорії Coal Reserves базуються на найбільш достовірній кількості Indicated та Measured Resources.
СПІВСТАВЛЕННЯ КРИТЕРІЇВ ВИЗНАЧЕННЯ ТА ОЗНАК КЛАСИФІКАЦІЇ ЗАПАСІВ І РЕСУРСІВ У ВІТЧИЗНЯНІЙ ТА МІЖНАРОДНІЙ ПРАКТИЦІ ГЕОЛОГО-ЕКОНОМІЧНОЇ ОЦІНКИ НА ПРИКЛАДІ РОДОВИЩ ВУГІЛЛЯ
Keywords: geological and economic evaluation of deposits; coal reserves; classification of reserves and resources; commercial significance; international standards; геолого-економічна оцінка родовищ; запаси вугілля; класифікації запасів і ресурсів; промислове значення; міжнародні стандарти